Advancing sustainable healthcare: a concept analysis of eco-conscious nursing practices - Marwa Mamdouh Shaban; Majed Awad Alanazi; Huda Hamdy Mohammed; Fatma Gomaa Mohamed Amer; Hla Hosny Elsayed; Mohammed ElSayed Zaky; Osama Mohammed Elsayed Ramadan; Mohamed Ezzelregal Abdelgawad; Mostafa Shaban (BMC, 2024)
Abstract Background As the healthcare sector grapples with its environmental footprint, the concept of Eco-conscious Nursing emerges as a pivotal framework for integrating sustainability into nursing practice. This study aims to clarify and operationalize Eco-conscious Nursing, examining its attributes, antecedents, consequences, and providing operational definitions to guide future research and practice. Methods Utilizing a systematic literature review across PubMed, Google Scholar, and CINAHL Ultimate, this study identifies and analyzes existing theories, frameworks, and practices related to eco-conscious nursing. Through conceptual analysis, key attributes, antecedents, and consequences of Eco-conscious Nursing are delineated, leading to the formulation of comprehensive operational definitions. Results The study reveals Eco-conscious Nursing as a multifaceted concept characterized by environmental stewardship, sustainable healthcare practices, and a commitment to reducing the ecological impact of nursing care. Operational definitions highlight the role of education, awareness, and institutional support as antecedents, with improved environmental health and sustainable healthcare outcomes as key consequences. Conclusion Eco-conscious Nursing represents a crucial ethos for the nursing profession, emphasizing the necessity of sustainable practices within healthcare. The operational definitions provided serve as a foundation for embedding eco-conscious principles into nursing, addressing the urgent need for sustainability in healthcare settings. Future research should focus on the empirical application of these definitions and explore the economic and cross-cultural dimensions of eco-conscious nursing.